2020
DOI: 10.3906/bot-1909-38
|View full text |Cite
|
Sign up to set email alerts
|

Aeropalynological survey in the city center of Aydın (Turkey)

Abstract: Airborne pollen grains in Aydın, an important city for agriculture and tourism in the western part of Turkey, were studied for 2 years (2014 and 2015) using the volumetric method. During a 2-year study conducted in the city center, an average of 19,226 pollen grains belonging to 46 taxa were detected. Among these detected taxa, 29 (average 73.97%) belonged to arboreal plants and 17 (average 24.95%) to nonarboreal plants. The highest pollen concentrations belonged to Olea europaea (21.02%), Quercus (15.23%), Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Bishan et al (2020) published the pollen concentrations in Zhanjiang, South China, and reported the correlation among pollen measurements with several factors, including temperature and relative humidity. Similarly, there have been publications reporting pollen measurements in various regions of Turkey such as Aydın, Muğla, Manisa, (Ulaş and Güvensen, 2019;Güvensen et al, 2020), İstanbul (Celenk et al, 2010) and Antalya (Tosunoglu et al, 2015). Olea was among the species that were examined in those publications.…”
Section: Airborne Pollen Forecasting Modelsmentioning
confidence: 96%
“…Bishan et al (2020) published the pollen concentrations in Zhanjiang, South China, and reported the correlation among pollen measurements with several factors, including temperature and relative humidity. Similarly, there have been publications reporting pollen measurements in various regions of Turkey such as Aydın, Muğla, Manisa, (Ulaş and Güvensen, 2019;Güvensen et al, 2020), İstanbul (Celenk et al, 2010) and Antalya (Tosunoglu et al, 2015). Olea was among the species that were examined in those publications.…”
Section: Airborne Pollen Forecasting Modelsmentioning
confidence: 96%
“…Polenler "Alerjik Bünyeli" insanlarda alerjik hastalıklara neden olabilmektedir (3). Polen alerjisinin görülme sıklığı ve etyolojisi bölgeler arasında değişmekte olup İzmir gibi polenden zengin Ege ve Akdeniz coğrafi bölgelerinde sıklığının %20'lere kadar yükseldiği tahmin edilmektedir (4,5).…”
Section: Introductionunclassified
“…If the types and concentration of the airborne pollen grain in the atmosphere are determined during periods when the symptoms of allergic diseases begin, intensify and end, better results may be obtained in diagnosis and treatment of pollen allergy. As in developed countries, the presence and concentration of allergen pollen grain in the atmosphere in many regions of Turkey has been analysed by using gravimetric and volumetric methods (Aytuğ et al, 1971;Potoğlu Erkara et al, 2007;Kızılpınar et al, 2012;Çeter et al, 2012;Öztürk et al, 2013;Çetin et al, 2015;Türkmen et al, 2018, Alan et al 2018aÖzler, 2019Özler, , Kılıç et al, 2019Alan et al, 2020;Güvensen et al, 2020, Çakır & Doğan, 2020.…”
Section: Introductionmentioning
confidence: 99%